Exposure to a Multitude of Environmental Chemicals During Pregnancy and Its Association with the Risk of Gestational Diabetes Mellitus - Yuzhe Lin; Xiong-Fei Pan; Maohua Miao; Huicai Guo; Peipei Meng; Wei Huang (Toxics)
Gestational exposure to environmental chemicals has long been considered an important contributor to adverse pregnancy outcomes. While humans are exposed to a large complexity of environmental chemicals under real scenarios, existing studies have generally focused on a limited number of substances when exploring the health impacts of environmental exposure. Our work employed the recently developed ExpoNano strategy to characterize exposure to 283 environmental chemicals via urine in pregnant women from three Chinese cities and explored the association between environmental exposure and the risk of gestational diabetes mellitus (GDM) through a nested case–control study within a prospective birth cohort. The results revealed ubiquitous gestational exposure (detection frequency > 70%) to 37 chemicals, including selected mono-phthalate esters (mono-PAEs), non-PAE plasticizers, synthetic antioxidants, organophosphate esters, personal care products, UV stabilizers, photoinitiators, pesticides, and hydroxy polyaromatic hydrocarbons across the three cities. The cumulative concentrations of detectable chemicals displayed median values of 461–741 ng/mL in different populations of pregnant women, which exhibited significant variations across regions. In the GDM case–control study (85 GDM cases and 170 healthy controls), although mixed exposure was not associated with the risk of GDM, exposure to acetyl tributyl citrate, an emerging plasticizer, was found to be significantly associated with GDM risk, based on both the single-pollutant and mixed exposure models. However, it should be noted that due to the relatively small sample size, the findings should be interpreted as preliminary exploratory results requiring further validation in larger cohorts. This study demonstrates the complexity of environmental chemical exposure during pregnancy, indicating a critical need for further investigations of the potential impact on pregnancy outcomes.